Open Source Sensor Interface for Soft Detectors in Surgical Simulators - Thomas Thurner; Roland Pruckner; Martin Kaltenbrunner; Andreas Schrempf (IEEE Access)
Surgical simulation is an emerging area of research and development, making new developments of especially hybrid simulators highly relevant. In this context, soft sensors enable low-cost position or force detection in haptically realistic synthetic tissue imitations to link the physical and virtual components of a patient phantom. To accelerate and facilitate the development of such simulators, an open-source sensor interface module optimized for use with soft carbon black silicone composite based sensors is presented. The module can measure complex voltages and impedances between multiple measurement channels at various frequencies. This enables up to three-dimensional tool tracking of conductive surgical instruments in patient phantoms as well as force or deformation detection at relevant structures. Several application scenarios are presented. Disruptive influences on the sensors are minimized by evaluating the signals based on discrete Fourier transform. Higher frequency signal coupling avoids contacting problems with soft sensors, which are often highly piezoresistive. Compensation functions or favorable sensor structures can largely avoid the influence of parasitic capacitances, which are particularly prevalent in low-cost electronics. The universally applicable module provides all the necessary electronics, including firmware and software interface for the subsequent processing computer. The handy module offers 17 measuring channels as well as digital inputs and outputs and is operated via USB. In addition to the evaluability of various sensor types relevant for surgical simulation, electroimpedance tomography is also supported, as demonstrated by the examples.